THE IMPACT OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON INVESTMENT DECISION IN MANADO - Nugraha, Faris Muchsin; Tulung, Joy E.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
The financial sector has an important role to improve people's welfare and encourage global economic growth. Financial literacy and financial inclusion, as two of the three pillars contained in the consumer empowerment trilogy, every pillar has a close correlation with another. This correlation has a direct proposition correlation. This study aims to see the effect of literacy and inclusion on financial investment decisions in Manado, either only partially or simultaneously. This research is quantitative research with a multiple linear regression method. The data were collected by distributing questionnaires to 100 respondents in Manado and its surroundings. The population in this research are all citizens of Manado who have financial investment instruments. This research has results: 1) financial literacy and financial inclusion have a simultaneous and significant influence on investment decisions in Manado. 2) Variable financial literacy partially affects investment decisions very significantly. 3) Variable financial inclusion affects the investment decision variable partially and significantly in Manado. The conclusion of this research is financial literacy and financial inclusion are indeed important things in developing the financial sector, including investment. In the city of Manado itself, it has been proven that financial literacy and inclusion can affect the quality of an investment.Â Keyword: financial literacy, financial inclusion, investment decision, consumer empowerment trilogy